O impacto da atuação das organizações da sociedade civil no processo de negociação de tratados e resoluções internacionais - Christo, Renata Costa de (2006)
That work objective to analyse the limites of acting from organization of civil society in definition of treaties and international solution. To much, developed an analysis about elements that permeate acting of participate phenomenons that emerge in scene of current process of globalization (chapter I). In second moment ( Chapter II) demonstrate the impact and limits acting of actors don't nationalized in international having the power spheres to decide, starting of analysis of dialogue instruments and participation of civil society ,conceived in level of economic cooperation organization of United Nations and having the power to decide authorities of MERCOSUL . The actuation transnationalized of citizen activism determined the insertion of news standard of cooperation and to decision in sphers of international organization, enlarging the prospect of construction of universal covering of citizenship rights.